Fusarium wilt of banana, a recurring threat to global banana production - Drenth, Andre; Kema, Gert; Dita Rodriguez, Miguel Angel; Jansen, Kees; Vellema, Sietze R.; Stoorvogel, Jetse (Frontiers Media, 2020)
TR4 first emerged in Southeast Asia (Ploetz, 1990) and its current rapid spread was analysed by Ordóñez et al. (2015). Subsequent studies showed that the TR4 strain is extremely virulent towards many banana cultivars, including Cavendish cultivars grown in large-scale monoculture plantations for export markets and many banana varieties important for food security and domestic consumption. There are no readily available solutions to manage this disease. Moreover, this global threat connects export trade, strongly dependent on the susceptible Cavendish cultivars, to local production systems wherein a range of banana varieties contributing to food security are also impacted.This research topic aims to provide a platform for information exchange and knowledge sharing. The contributions demonstrate an active research community in search of effective control of FWB. Taken together, the papers provide an overview of our current understanding of the biology and epidemiology of TR4, its management and how integrated and innovative solutions are required and need to be embraced by all stakeholders in an effort to build a sustainable banana industry for the future.